Mancala board games and origins of entrepreneurship in Africa. - Maxwell Mkondiwa (PLoS ONE, 2020)
This study examines the correlational relationship between the historical playing of indigenous strategic board games (also called mancala) and the socio-economic complexity of African ethnic groups as well as the incidence of entrepreneurial pursuits. Anthropology literature suggests that these games may be associated with socio-economic complexity of the ethnic groups-the so-called games in culture hypothesis. I revisit this hypothesis with better data and motivated by anecdotal evidence, introduce a contemporary hypothesis, origins of entrepreneurship hypothesis-that descendants of societies that played complex mancala games are more likely to be engaged in non-farm self-employment today. I compile the first comprehensive database of mancala games in Africa matched to ancestral characteristics data, and for 18 African countries, to the Afrobarometer survey data. Using historical and contemporary data, I do not find evidence for either hypothesis. Despite the null results, I explore how related hypotheses and studies can build on the comprehensive mancala database.